2011
DOI: 10.1016/j.neuropsychologia.2011.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of the Enigma illusion: A transcranial magnetic stimulation study

Abstract: The aim of this study was to test the role of the visual primary (V1) and the middle temporal area (V5/MT) in the illusory motion perception evoked by the Enigma figure. The Enigma figure induces a visual illusion that is characterized by apparent rotatory motion in the presence of a static figure. By means of repetitive transcranial magnetic stimulation (rTMS) we show that V5/MT is causally linked to the illusory perception of motion. When rTMS was applied bilaterally over V5/MT just prior to presentation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In order to pursue that goal a sensitivity task employing specific motion illusions (i.e., Gori and Hamburger, 2006; Gori et al, 2006, 2010b, 2011; Gori and Yazdanbakhsh, 2008; Yazdanbakhsh and Gori, 2008, 2011; Hamburger, 2012) could be devised given the fact that this kind of illusory motion is processed by V5/MT (Ruzzoli et al, 2011). Potential differences in this task could not be related to a general perceptual noise exclusion deficit.…”
Section: Discussionmentioning
confidence: 99%
“…In order to pursue that goal a sensitivity task employing specific motion illusions (i.e., Gori and Hamburger, 2006; Gori et al, 2006, 2010b, 2011; Gori and Yazdanbakhsh, 2008; Yazdanbakhsh and Gori, 2008, 2011; Hamburger, 2012) could be devised given the fact that this kind of illusory motion is processed by V5/MT (Ruzzoli et al, 2011). Potential differences in this task could not be related to a general perceptual noise exclusion deficit.…”
Section: Discussionmentioning
confidence: 99%
“…The two fMRI studies that directly investigated the RSI3031 recorded an increase in neural activity in the motion-sensitive area of the human visual cortex during the observation of the RSI, suggesting that local motion signals in response to asymmetric spatial patterns at the level of V1 are integrated in the motion-sensitive cortical area (V5-MT complex) that creates the vivid rotatory motion perception. Global rotation is a peculiar type of motion that requires specifically V5-MT activity, no matter whether it is real32 or illusory21. The V5-MT complex possess neurons with large receptive fields that are able to integrate, into a global motion, the local motion signals processed by the small receptive fields of the DS neurons populating V1.…”
Section: Discussionmentioning
confidence: 99%
“…from that present in the physical stimulus; or, even more strikingly, the perception of motion is induced by a completely static pattern131415. As regards this latter family of stimuli, neurobiological and behavioral studies showed that both fixational eye movements161718 and cortical processing192021 are responsible for the perception of motion, but some outstanding questions remain unsolved. In particular, there is considerable debate among investigators as to whether gaze instability is strictly necessary to the illusory motion perception or, rather, if fixational eye movements only improve the strength of the illusion.…”
mentioning
confidence: 99%
“…Tadin et al (2011) succeeded in reducing the surround suppression at V5 by rTMS, revealing spatial summation of motion in a large visual field. Ruzzoli et al (2011) found that rTMS targeting V5 weakened the illusory stream perception of Enigma. Whether rTMS targeting V5 also erases the present illusion or not could be a direct test of the centre-surround relative-motion detector hypothesis.…”
Section: Discussionmentioning
confidence: 97%